Africa and the North - Engel, Ulf; Rye Olsen, Gorm; Engel, Ulf; Rye Olsen, Gorm (Taylor & Francis, 2005)
An important new discussion of Africa's place in the international system. This volume discusses Africa's place in the international system, examining the way in which the Westphalian system, in light of the impact of globalization and transnational networks, continues to play a major role in the structuring of Africa's international relations. The book provides a solid empirical analysis of key global players in Africa - France, the UK, the US, Japan, Germany, the EU and the UN - and of their policies towards the region. In the context of the 'war against terrorism', African political stability becomes a consideration of increasing importance. By analyzing the relevance of the states in the North, this book challenges conventional wisdom in recent international relations thinking. It applies the concept of an 'international policy community' to bridge the gap between the 'domestic' and the 'international', explaining why Africa retains a role in global politics out of any proportion to its economic weight.
English
Keywords: African history; Politics & government; International relations; policy; african; states; sierra; leone; sub-saharan; africas; international; relations; french